CANCER SCREENING AMONG OLDER LATINA AND AFRICAN AMERICAN WOMEN: EFFECTIVENESS OF COMMUNITY-BASED OUTREACH - Bullock, K (Innov Aging, 2018)
Objectives To explore the effectiveness of an interdisciplinary team approach to screening low income, community dwelling, women of diverse racial backgrounds Methods An exploratory study was conducted in seven senior housing neighborhoods across urban and rural communities. 150 women received cancer care education as enhanced intervention (n = 100) by random assignment of the community outreach visit or received the standard outreach consisting of a psychosocial assessment and referral (n = 50). The Theory of Planned Behavior (TPB) informed and guided this study. A low literacy component of the intervention included pictures and various language dialectic adjustments to the narratives used to explain the importance of cancer screening among older women. Attitude toward behavior, subjective norms, and perceived behavioral control, were examined to understand individual behavioral intentions and action. SPSS used to conduct three-level mixed-effects modeling to determine the effectiveness Results The intervention group had significantly fewer barriers (attitudes, norms and perceived control) to completing a cancer screening exam (adjusted mean difference − 8.25, 95% CI − 13.41 to − 0.20) and a significant reduction low literacy scores (intermediate outcome) (95% CI 0.06–0.94) compared to women in the standard outreach group. No significant differences were found for social support, health insurance coverage, symptoms of depression, number of chronic illnesses, years of school completed (education level) or career occupation type. Conclusions This study shows that community-based cancer screening intervention that includes a culturally specific education component is effective in a population of low-income, older, community-dwelling, women of diverse racial backgrounds.